Effect of Ohmic Heating on the Extraction Yield, Polyphenol Content and Antioxidant Activity of Olive Mill Leaves - Fereshteh Safarzadeh Markhali; José A. Teixeira; Cristina M. R. Rocha (Clean Technologies, 2022)
This study examined the influence of ohmic heating (OH), compared to the conventional heating (Conven) and Control (solvent) methods, on the extraction of olive mill leaves. The main extraction parameters were: (i) solvent ratio (aqueous ethanol; 40%, 60%, and 80%, v/v), and (ii) extraction temperature; 45 °C, 55 °C, and 75 °C (for OH and Conven), and room temperature (for Control). The selected response variables were extraction yield (%), total phenolic content (TPC), and antioxidant activity (ABTS and DPPH). The ohmic system, compared to Conven and Control, exhibited the greatest effects (p < 0.001) on increasing (i) extraction yield (34.53%) at 75 °C with 80% ethanol, (ii) TPC at 55 °C (42.53, 34.35, 31.63 mg GAE/g extract, with 60%, 40%, and 80% ethanol, respectively), and (iii) antioxidant potency at 75 °C detected by DPPH and ABTS, in the range of 1.21–1.04 mM TE/g, and 0.62–0.48 mM TE/g extract, respectively. Further, there were relatively similar trends in TPC and antioxidant activity (both methods), regardless of solvent ratios, p < 0.001. These findings demonstrate the potential of ohmic heating, as a green processing tool, for efficient extraction (15 min) of olive leaves. To date, no literature has described ohmic application for olive leave extraction.